Relationship between scientific paradigm and research front. On Example of Information Science Research Production - Pečarić, Đilda (Array, 2009)
Empirical indicators about time distribution and „obsolescence“ of cited references are retrieved from doctoral dissertations in Information Science from 1978 to 2007 at Croatian universities. Cluster of most cited authors who are recognized as key authors for Information Science paradigm is gained from citation and co-citation analysis. Domination of these authors constitutes “conceptual knowledge zone” which is placed according to time distribution at the end of axes of obsolescence of cited literature. As opposed to that, research front, which is the period of most intensive research activity, is placed in the first time quarter (from zero to four years old cited literature), and there are 10% of most cited authors. Our research follows transit of researcher from research front to zone of paradigmatic knowledge. Hypothesis is that new authors who enter conceptual knowledge zone suppress “old” authors ; so it can be concluded that incomers in conceptual knowledge zone are holders of new theoretical approaches and solutions for new problems. Duration and importance of “old” authors ensure paradigm and methods for solution of “old” problems, respectively for the production of professional papers and traditions of profession.